11.1k views
0 votes
50 points, question is below.

50 points, question is below.-example-1
User John Spong
by
5.0k points

2 Answers

3 votes

Answer:

2

Explanation:

Given function to us is ,


\implies f(x) =( x +5)/( x^2+3x -10)

Here the denominator should not be equal to 0 . Therefore ,


\implies x^2 + 3x -10 \\eq 0\\\\\implies ( x +5)(x-2) \\eq 0 \\\\\implies x \\eq 5 , -2

We can simplify the function and write it as ,


\implies f(x) =( x +5)/( x^2+3x -10)\\\\\implies ( ( x +5))/( ( x +5)(x-2))\\\\\implies (1)/(x-2)

Therefore our required answer is 2 .

User Zakoff
by
5.9k points
2 votes


x^2+3x-10\\eq0\\\\x^2+5x-2x-10neq0\\\\x(x-5)-2(x+5)\\eq0\\\\(x+5)(x-2)\\eq0\to x+5\\eq0\ \wedge\ x-2\\eq0\\\\x\\eq-5\ \wedge\ x\\eq2\\\\(x+5)/(x^2+3x-10)=(x+5)/((x+5)(x-2))=(1)/(x-2)\\\\Answer:\ x=2

User Vibhas
by
5.5k points